Peningkatan Kapasitas Paralegal dalam Pemberian Bantuan Hukum di Desa Deme Dua dan Desa Bubalango Berdasarkan Peraturan Menkumham No. 1 Tahun 2018 - Roy Marthen Moonti (Jurnal Kabar Masyarakat, 2025)
The provision of legal aid is a fundamental right for every citizen, as regulated in Law No. 16/2011 on Legal Aid. However, the limited number of advocates in rural areas such as Deme Dua and Bubalango Villages makes access to justice for the poor difficult. MOLHR Regulation No. 1/2018 recognizes the role of paralegals in assisting the provision of legal aid, both litigation and non-litigation. This research aims to increase the capacity of paralegals to play a more effective role in helping communities access justice. The research method used was a qualitative approach with observation, interviews, and case study-based training. The results showed that improving paralegals' legal understanding and advocacy skills contributed significantly to expanding access to legal aid in the region. In conclusion, strengthening the capacity of paralegals can be an alternative solution in overcoming the limitations of legal services in rural areas.